2013
DOI: 10.1007/s10549-013-2556-4
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3-positive regulatory T lymphocytes and epithelial FOXP3 expression in synchronous normal, ductal carcinoma in situ, and invasive cancer of the breast

Abstract: FOXP3-expressing T regulatory lymphocytes (Tregs) have been described as putative mediators of immune tolerance, and thus facilitators of tumor growth. When found in association with various malignancies, Tregs are generally markers of poor clinical outcome. However, it is unknown whether they are also associated with cancer progression. We evaluated quantitative FOXP3 expression in lymphocytes as well as in epithelial cells in a set of thirty-two breast tumors with synchronous normal epithelium, ductal carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 28 publications
6
36
0
Order By: Relevance
“…Overall, higher numbers of Tregs were found in DCIS than in normal breast tissue, with the highest number found in invasive breast carcinoma (29). Similar findings were reported by Lal and colleagues (30). Interestingly, Treg infiltration in pancreatic cancer also appears to increase from normal tissue to preinvasive lesions to invasive adenocarcinoma (31).…”
Section: Discussionsupporting
confidence: 85%
“…Overall, higher numbers of Tregs were found in DCIS than in normal breast tissue, with the highest number found in invasive breast carcinoma (29). Similar findings were reported by Lal and colleagues (30). Interestingly, Treg infiltration in pancreatic cancer also appears to increase from normal tissue to preinvasive lesions to invasive adenocarcinoma (31).…”
Section: Discussionsupporting
confidence: 85%
“…Previous genomic characterization of DCIS cases have identified gene expression signatures implying the presence of activated T cells in a subset of tumors (36), but this was not confirmed by any other method. Prior studies have also shown that the frequencies of Tregs increased during tumor progression suggesting that this could be used to predict risk of invasive progression (13). However, in our experience the frequency of FOXP3 + T cells is very low in DCIS (<10% of T cells) and their topologic distribution is highly variable within tumors making their accurate assessment inaccurate in thin tissue sections (see Supplementary Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Increased inflammation in DCIS is associated with high nuclear grade, HER2 positivity, and extent of lesions [30,31]. FoxP3+ Tregs have been identified in DCIS lesions, although they were not associated with grade [32]. Esserman and coworkers found that CD68 + macrophages were associated with large, pathologically dense, high-grade DCIS lesions with comedonecrosis [13].…”
Section: Introductionmentioning
confidence: 99%